Regiochemical Control of Pyrazoles by Solvent and β‐Enamino Diketone Structure: Regioselective Synthesis of 4, 5‐Disubstituted N‐Phenylpyrazoles. Issue 5 (13th March 2017) - Souza, Thiago F.; Silva, Michael J. V.; Silva, Raí G. M.; Gonçalves, Davana S.; Simon, Paula A.; Jacomini, Andrey P.; Basso, Ernani A.; Moura, Sidnei; Martins, Marcos A. P.; Back, Davi F.; Rosa, Fernanda A.
Abstract: A simple method for the regiocontrolled synthesis of the 4, 5‐disubstituted N ‐phenylpyrazole regioisomers2 and3 from β‐enamino diketones and phenylhydrazine is described. Pyrazole2 was prepared regioselectively by carrying out the reaction in a protic solvent, whereas pyrazole3 was obtained as the main product by using an aprotic solvent. Steric factors regarding the β‐enamino diketones also influenced the regiochemistry of2 and3 . The influence of solvent on the reaction outcome can be rationalized by using Fukui indices. The structures of2 and3 were unambiguously elucidated by 1 H and 13 C NMR spectroscopy, two‐dimensional HMBC experiments, high resolution mass spectrometry, and X‐ray crystallographic analysis. Abstract : This way or that ! A regiocontrolled synthesis of 4, 5‐disubstituted N ‐phenylpyrazoles from unsymmetrical β‐enamino diketones in either protic or aprotic solvent has been developed. A series of regioisomers of 4, 5‐disubstituted N ‐phenylpyrazoles have been prepared this way.